IL-17A exacerbates fibrosis by promoting the proinflammatory and profibrotic function of orbital fibroblasts in TAO - Fang, S; Huang, Y; Wang, S; Zhang, Y; Luo, X; Liu, L; Zhong, S; Liu, X; Li, D; Liang, R; Miranda, P; Gu, P; et al. (Oxford University Press, 2016)
Context: The development of thyroid-associated ophthalmopathy (TAO) is associated with self-immune dysfunction. Recent findings in TAO and Graves' disease indicate that IL-17A may also be involved in the autoimmunity of TAO.